1990
DOI: 10.1093/ije/19.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Mammographic Parenchymal Patterns with Breast Cancer Risk Factors and Risk of Breast Cancer in a Prospective Study

Abstract: A prospective study has been conducted on 4954 female volunteers from the Island of Guernsey between 1977 and 1985 to examine risk factors for breast cancer and their relationship to mammographic parenchymal patterns as assessed by Wolfe's method of grading. Up to September 1988, 69 women had developed breast cancer, 11 of whom were prevalent cases being diagnosed within six months of mammography. The remaining incident cases were diagnosed six to 126 months (median 65 months) after entry to the study. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
19
2
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 0 publications
7
19
2
1
Order By: Relevance
“…Other studies have reported a relationship between body weight and mammographic parenchymal pattern similar to our own (Brisson et al, 1984;de Waard et al, 1984;Grove et al, 1985;De Stavola et al, 1990;Boyd et al, 1995Boyd et al, , 1998Salminen et al, 1998). Boyd et al (1998) found that, in premenopausal women, weight and BMI were negatively correlated with the area of dense tissue.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies have reported a relationship between body weight and mammographic parenchymal pattern similar to our own (Brisson et al, 1984;de Waard et al, 1984;Grove et al, 1985;De Stavola et al, 1990;Boyd et al, 1995Boyd et al, , 1998Salminen et al, 1998). Boyd et al (1998) found that, in premenopausal women, weight and BMI were negatively correlated with the area of dense tissue.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown that increased body weight and body mass index (BMI) are associated with a significant reduction in the percentage of women having a P2 or DY (P2/DY) pattern (Brisson et al, 1984;de Waard et al, 1984;Grove et al, 1985;De Stavola et al, 1990;Boyd et al, 1995Boyd et al, , 1998Salminen et al, 1998). However, overweight women have an elevated risk of developing post-menopausal breast cancer (Tornberg et al, 1988;van den Brandt et al, 1997).…”
mentioning
confidence: 99%
“…The incidence of favorable mammographic parenchymal pattern was significantly related to old age, large BMI and multiparity. An association between mammographic parenchymal patterns using Wolfe's classification, and the risk of breast cancer has been found in many studies (Wolfe, 1976a;De Stavola et al, 1990;Kato et al, 1995). Women who had a mammographic pattern of severe involvement of ducts or dysplasia had a greater risk of breast cancer than women with parenchyma composed primarily of fat.…”
mentioning
confidence: 96%
“…Women who had a mammographic pattern of severe involvement of ducts or dysplasia had a greater risk of breast cancer than women with parenchyma composed primarily of fat. Some studies (De Stavola et al, 1990;Bartow et al, 1995;Beijerinck et al, 1991;Leinster et al, 1988;Saflas and Szklo, 1987) also found that mammographic parenchymal patterns correlate with risk factors of breast cancer. These studies represent cross-sectional data, where the occurrence of mammographic parenchymal patterns and the risk factors of breast cancer were measured simultaneously.…”
mentioning
confidence: 98%
“…To our knowledge, only one study (Ekbom et al, 1995) to date has investigated the potential role of perinatal characteristics and found a positive but nonsignificant association with birth weight. Inverse associations have been found between contemporaneous measures of adult adiposity and breast density (Brisson et al, 1984;Grove et al, 1985;Whitehead et al, 1985;De Stavola et al, 1990;Gram et al, 1997;Boyd et al, 1998;Sala et al, 1999), but associations with adult height have been less consistent (Brisson et al, 1984;Gram et al, 1997;Boyd et al, 1998;Sala et al, 1999). These studies were, however, limited to anthropometric measures relating to a single point in time, mostly at mammography, thus a detailed study of the effect of growth and life-course changes in body size could not be investigated.…”
mentioning
confidence: 99%